Nature and impact of women's participation in economic activities in rural Bangladesh: insights from household surveys - Mahabub Hossain; Manik Lal Bose; Alia Ahmad (Lund University, School of Economics and Management, Department of Economics, 2004)
Based on household-level data collected in 1987 and 2000 this paper first depicts the patterns and trends in womens work and secondly, analyses the factors that work behind gender division of labour in rural Bangladesh. An empowerment index is developed from the data on household decision-making in different spheres, and its relationship with womens work is then explored. The persistent gender division of labour in rural Bangladesh has been found to be associated with both economic factors - wage rates, access to production factors like land, micro credit, infrastructure) and socio-cultural factors - norms and customs regarding womens mobility and gender role in production and reproduction. Economic activities within the household have been found to have weak impact on empowerment. Two policy implications emerge from the study: 1. Promotion of female education to enable women to take part in market activities in the non-agricultural sector where gender disparity in earnings is less. 2. Investment in infrastructure that can facilitate womens mobility outside the household as well as can reduce the burden of domestic work.
Keywords: J16; J22; 330; ender division of labour; empowerment